ANALISIS YURIDIS PENGUPAHAN PADA SEKOLAH DASAR ISLAM TERPADU AL HAMIDIYYAH BOJONGGEDE KABUPATEN BOGOR - Ahmad Madroji; Rumainur (JOURNAL OF LAW AND NATION, 2023)
Because the characteristics of education are non-profit, the most appropriate form of legal entity is a foundation. According to article 1 point 1 of Law no. 16 of 2001 concerning Foundations as Amended by Law no. 28 of 2004 (Foundation Law), a foundation is a legal entity consisting of segregated assets and intended to achieve certain goals in the social, religious and humanitarian fields. A polemic arose regarding remuneration based on the Law on Teachers and Lecturers Number 14 of 2005 in article 15 paragraph 3 which reads as follows; 'Teachers appointed by education units organized by the community are given a salary based on a work agreement or collective bargaining agreement. Apart from that, there is a strengthening of article 21 of Government Regulation Number 36 of 2021 concerning Wages which reads; ``That the structure and scale of wages is an obligation that must be prepared and implemented by the Company with due regard to productivity and capabilities`. So with the clause mentioning 'Teacher remuneration by the Foundation is determined based on a work agreement or collective work agreement' based on laws and government regulations regarding wages, it becomes clear that remuneration practices in private schools are not standardized in terms of remuneration and moreover fulfilling the rights of teachers for a decent living.